Association of immune evasion in myeloid sarcomas with disease manifestation and patients’ survival - Bauer, Marcus; Monecke, Astrid; Hackl, Hubert; Wilfer, Andreas; Jaekel, Nadja; Bläker, Hendrik; Al-Ali, Haifa Kathrin; Seliger, Barbara; Wickenhauser, Claudia (Frontiers in Immunology, 2024)
Tumor samples of 45 patients from two centers with a diagnosis of myeloid sarcoma (MS) and paired bone marrow biopsies (BMBs) were stained for components of the human leukocyte antigen class I (HLA-I), as well as the antigen processing and presenting machinery (APM) and tissue infiltrating lymphocytes (TILs) using conventional immunohistochemistry (IHC) and multiplex immunohistochemistrymultispectral imaging (MSI). The publicly available RNA expression dataset GSE103344 originating from human AML cells with the in vitro and in vivo ability to form solid tumor mass served as an external reference for APM component expression. In addition, bulk RNA sequence analysis was performed from MS samples with preserved and decreased HLA-I expression. Higher APM expression and TIL infiltration was correlated with a superior survival of MS patients.